The association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and pulmonary function: evidence from NHANES 2007–2012 - Miaoyan Liu; Chaofeng Gao; Jinggeng Li; Yibo Zhang; Rui Gao; Chaoting Yang; Jian Zhang (Frontiers in Nutrition)
BackgroundThis research aims to explore the potential association between lung function and the ratio of non-high-density lipoprotein cholesterol (NHL) to high-density lipoprotein cholesterol (NHHR). Previous research has shown that lipid metabolism imbalance is closely linked to cardiovascular disease, however, there is a lack of information regarding its impact on lung function.MethodsThis research used information from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2007 to 2012, including a large-scale sample of 9,498 adults aged 20 years and older. A cross-sectional study employing multivariable regression models was aimed at examining the relevance between NHHR and indicators of lung function (FEV1, FVC, and FEV1/FVC). Adjustments were made for a wide range of confounding factors, encompassing race, gender, age, BMI, smoking status, physical activity, diabetes, alcohol consumption, and education level. Data analysis included categorizing NHHR into quartiles and using trend tests to evaluate dose–response relationships between NHHR quartiles and lung function. Sensitivity analyses were conducted by excluding participants with asthma and COPD to ensure the reliability of the results.ResultsThe results manifested a significant correlation between decreased FEV1 and FVC values and elevated NHHR, most notably within the highest quartile of NHHR (Q4), where the association was most pronounced. Additionally, trend test results indicated a significant linear negative correlation between NHHR and both FEV1 and FVC. However, the correlation between FEV1/FVC and NHHR showed a nonlinear U-shaped pattern. Suggesting differential impacts of NHHR on various lung function indicators. The findings’ robustness was shown by sensitivity analysis, which revealed that even after omitting people with asthma and COPD, the negative correlation between NHHR and FEV1 and FVC remained significant.ConclusionThis research emphasizes the significance of tracking lipid levels in evaluating respiratory health and offers early evidence in favor of NHHR as a probable biomarker for respiratory function. Further longitudinal research has occasion to prove the causal relationship between NHHR and lung function and to explore its underlying biological mechanisms.